DEKOMPOSISI TENAGA KERJA: SUMATERA UTARA - Dahlan Tampubolon (JIP ( Jurnal Industri dan Perkotaan ), 2006)
Eployment as an element of regional economic structured can be show held by decomposition method or shift-share analysis. This study used data employment from statistical of people welfare 1993-2003